Manejo integrado de Tuta absoluta Meyrick, en el cultivo de tomate Solanum lycopersicum Miller - Armijo Rodríguez, Steeven Elías (2024)
This document aims to describe the integrated management of the tomato moth Tuta absoluta, which emerges as a significant threat to tomato production worldwide. This research covers the description of the damage and the determination of the most efficient methods for the control of T. absoluta. The damage caused by the tomato moth is diverse and ranges from perforation of fruits and shoots to their infestation with excrement, which significantly reduces the quality and yield of crops, in studies carried out in tomato fields. , it is estimated that when infestation levels in plants reach around 20%, damage can already be observed in the fruits, which represent approximately 8%. The tomato, a plant native to America, apparently comes from the mountainous areas of Peru , Ecuador and Chile. It is a herbaceous plant agent with a seed stem and a root system consisting of a short main root, which branches into numerous secondary roots. The impact caused by the tomato moth on tomato crops can be extremely detrimental to the crop. By damaging the leaf structures, the plant loses its ability to properly carry out photosynthesis. In Ecuador, it occupies fourth place in importance in terms of planting area within vegetable crops, with 3,210 hectares cultivated. The average yield ranges between 18 and 20 tons per hectare. .